Predictive value of immunological markers after bacille Calmette–Guérin induction in bladder cancer. (13th September 2021) - Elsawy, Amr A.; Abol‐Enein, Hassan; Laymon, Mahmoud; Ahmed, Asmaa E.; Essam, Ahmed; Hamam, Eman T.; Zidan, Abdel‐Aziz A.; Zahran, Mohamed H.; Shokeir, Ahmed A.; Awadalla, Amira
Abstract : Objectives: To investigate the predictive value of different immunological markers on treatment outcomes after bacille Calmette–Guérin (BCG) induction in high‐risk non‐muscle‐invasive bladder cancer (NMIBC). Patients and Methods: Patients who underwent transurethral resection of bladder tumour for NMIBC were assessed for study eligibility. Urine and blood samples were taken from patients at baseline (immediately before first dose of induction) and after induction (4 h after last [sixth] dose). Urine samples were evaluated for interleukin (IL)‐2 and IL‐10 by solid‐phase enzyme‐linked immunosorbent assay. Blood samples were evaluated for tumour necrosis factor α (TNF‐α), cytotoxic T‐lymphocyte antigen 4 (CTLA‐4) and transcription factors (TFs) (GATA‐binding protein 3 [GATA3], T‐box expressed in T cells [T‐bet], and forkhead box protein 3 [FoxP3]) using quantitative reverse transcriptase‐polymerase chain reaction analysis. Change pattern and fold change of each evaluable marker was assessed in relation to different treatment outcomes (initial complete response [ICR]/recurrence/progression). Results: Between July 2013 and May 2019, 204 patients were included. Among evaluable markers, urinary IL‐2 and serum TNF‐α increased in all patients, serum CTLA‐4 and FoxP3 + showed a predominant decreased pattern in 188 (92.2%) and 192 (94.1%) patients, respectively. An ICR was achieved in 186 (91.2%) patients. Serum TNF‐α fold change and urinary IL‐10 change pattern were significantly associated with an ICR ( P  = 0.001 and P  = 0.03, respectively). At a median (range) follow‐up of 37 (20–88) months, 104 (56%) patients developed recurrence. Urinary IL‐10, serum CTLA‐4, T‐bet +, FoxP3 + change patterns and GATA3 + /T‐bet + ratio were significantly associated with tumour recurrence ( P  = 0.001, P  = 0.001, P  = 0.02, P  = 0.009 and P  = 0.001, respectively). Tumour progression occurred in 34 (18.3%) patients. Urinary IL‐10, serum CTLA‐4, serum T‐bet + change patterns and GATA3 + /T‐bet + ratio were independent predictors of tumour progression ( P  = 0.001, P  = 0.001, P  = 0.02 and P  = 0.001, respectively). Conclusions: Urinary IL‐10 and serum TNF‐α can significantly predict ICR. Moreover, change pattern of urinary IL‐10, serum CTLA‐4, TFs (GATA3, T‐bet and FoxP3) and GATA3 + /T‐bet + ratio after BCG induction can independently predict further BCG response. These markers could be implemented in clinical practice when management options are discussed or in systems with severe BCG shortage.